The Use of Analytical Hierarchy Process in Identifying Weight age Criteria for Academic Staff Selection - Norsyafawati W. Muhamad Radzi, Wan; Nordin, Norshahrizan; Ramli, Razamin; Abashah, Aidanazima; Nurshahrizleen Ramlan, Sayang (International Journal of Engineering and Technology, 2018)
The academic staff selection for any organization is an important process that involves in decision making process. The process must be carried out carefully because it involves some important aspects towards the staff selection. During the interview session, the selection process based on five criteria of the applicant. The five selection criteria consists of academic qualification, religious knowledge, community services, knowledge, and communication skills. Furthermore, the selection of applicants for the academic ability and suitability with the field in order to make the selection process is becoming more complex. The selection of the applicants for academic staff also relies on judgments of the committee that was appointed for interviewing the applicants with a lot of experience in the selection of academic staff applicant. The study finds that the objectives are to identify all criteria relevant to the selection of staffs. The technique used in giving weights to each criterion is Analytical Hierarchy Process (AHP) technique. As a result, the highest weight was assigned to the first criteria which are academic qualification with the weight 0.3423. It shows that the academic qualification was the most important criterion compared to the other criteria. In addition, the selection of applicant for academic staff is able to assist in the selection of potential qualified academic staff.